Mir-184 Contributes to Brain Injury Through Targeting PPAP2B Following Ischemic Stroke in Male Rats - Yang, Huajun; Zhang, Yifan; Chen, Hongqun; Zhu, Yingwu; Li, Yuan; Ouyang, Fu; Chu, Lan; Liu, Daishun (Frontiers in Molecular Neuroscience, 2021)
Our previous study revealed that miR-184 expression is significantly altered in the brain following ischemic stroke in rats. However, it is unknown whether this alteration in miR-184 expression contributes to brain injury after ischemic stroke. Here, we aim to address the potential of miR-184 to impact nerve injury following ischemia and reperfusion. Rats received ICV injection of miR-184 adenovirus or empty vector and were subjected to right middle cerebral artery occlusion (MCAO) to establish an ischemic stroke model. We cultured SH-SY5Y cells under oxygen-glucose deprivation/reoxygenation (OGD/R) and transfected them with miR-184 lentivirus to explore the primary mechanisms. To evaluate miR-184 expression, neurological function deficits, the cerebral infarct volume, cell viability, and apoptosis, qRT-PCR analysis of miR-184 expression, the modified neurological severity score (mNSS) system, TTC staining, the CCK-8 assay, flow cytometry, and dual-luciferase reporter assays were utilized. We found that miR-184 expression was downregulated and that the cerebral infarct volume and mNSSs were increased following ischemic stroke; however, increasing the level of miR-184 alleviated brain damage. Overexpression of miR-184 resulted in increased viability and reduced apoptosis of SH-SY5Y cells following OGD/R in vitro. We identified the phosphatidic acid phosphatase type 2B (PPAP2B) gene as a direct target gene of miR-184. In summary, our results reveal that attenuation of miR-184 levels in ischemic stroke contributes to ischemic injury through targeting PPAP2B mRNA-mediated apoptosis, which may be a promising therapeutic target for ischemic stroke.